TRANSFORMATION OF GREEN AREAS IN SPORT, LEISURE AND CULTURE SPACES: MARK OF IDENTITY OF THE CITY OF CURITIBA (Fiep Bulletin - online, 2015)
The reflection that we develop adopts as object of analysis the city of Curitiba, that contemplates privileged spaces close to the nature for experiences in the scope of the sport, the leisure and the culture. The adopted clipping objective to detach the importance of these spaces for the urban materiality, which can associate corporal practices with significant experiences in the scope of the culture, making possible a direct contact between the people, being able to consist in meeting points of the local community, thus with a new urban life style, printing a "mark of identity" to the city.
Keywords: Leisure; sport; space.